Potency of surface layer protein from Lactobacillus sp. as drug nanocarriers - Yuliawati Yuliawati, Diah Anggraini Wulandari, Ni Wayan Sri Agustini, Asrul Muhamad Fuad, Trisanti Anindyawati, Mega Ferdina Warsito, Riyona Desvy Pratiwi (Journal of Applied Pharmaceutical Science, 2024)
Surface layer protein (SLP) is the outboard structure of bacteria which controls their adaptability and adherence to other bacteria and biological surfaces. SLP could maintain its 3D structure and has a self-assembly mechanism, even after being isolated from the host microorganism. This protein is potential to be integrated into drug nanocarriers because it has size in nanometer, protective features, self-assembly capacity, and high compatibility either with biological systems or chemical substances. It has been used as a surface coating for liposomes, emulsomes, polymeric nanoparticles (NPs), metal NPs/nanocomposites, or as a direct nanocarrier of small molecules. Moreover, SLP significantly improved the physicochemical properties of the drug delivery system (higher stability and longer half-life) and synergic bioactivities (increasing intestinal absorption; protecting against the acidic gastric environment; enhancing immune response, antibiofilm, and antibacterial activity). Additionally, the integration of SLP into a drug delivery system is simple and sustainable. In this review, references were searched in Scopus, PubMed and Google Scholar engines by using the terms “surface layer protein,” “SLP,”,“drug carrier,” “drug delivery,” “Lactobacillus,” and “nanomedicine.” To the best of our knowledge, this work is the first review of the applications of the SLP as drug nanocarriers.
Keywords: SLP, drug delivery, nanomedicine, Lactobacillus, drug carrier